KarstMod: A modelling platform for rainfall - discharge analysis and modelling dedicated to karst systems. (December 2019) - Mazzilli, N.; Guinot, V.; Jourde, H.; Lecoq, N.; Labat, D.; Arfib, B.; Baudement, C.; Danquigny, C.; Dal Soglio, L.; Bertin, D.
Abstract: We propose an adjustable modelling platform (KarstMod) for both the simulation of spring discharge at karst outlets and analysis of the hydrodynamics of the compartments considered in the model. KarstMod provides a modular, user-friendly modelling environment for educational, research and operational purposes. It can reproduce the structure of most conceptual lumped models of karst systems in the literature. The modularity of the platform allows to compare different hydrosystems within the same methodological approach. To promote good modelling practices, the platform provides a variety of graphs and tools that facilitate improved understanding and insights in the behaviour of the models, and that detect possible flaws in structure and parameterization. The model and users manual are freely downloadable from the SNO Karst website (www.sokarst.org ).